Judge's Decision on Child Crimes - Sulastri Arfan Gani (Estudiante Law Journal, 2023)
This study aims to determine judges’ decisions on criminal acts of juvenile delinquency. The method used in this study is normative research methodology and uses a statutory and shirt approach as well as descriptive analysis techniques. The results of this study indicate that the judge's considerations in deciding cases of crimes of violence committed by children can be seen from the two decisions by looking at the facts of the trial where the evidence submitted by the public prosecutor and the evidence was acknowledged by the defendant and also looking at the testimony of witnesses which also adds to the arguments against the defendant so that in the court process the judge is stronger in the judge's conviction to decide on the case on a fair basis seeing in the defendant, the judge does not find justification or pardon that can relieve the defendant from his case so that he must be held accountable.